2014
DOI: 10.1016/j.jpsychires.2014.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Association of low-activity MAOA allelic variants with violent crime in incarcerated offenders

Abstract: The main enzyme for serotonin degradation, monoamine oxidase (MAO) A, has recently emerged as a key biological factor in the predisposition to impulsive aggression. Male carriers of low-activity variants of the main functional polymorphism of the MAOA gene (MAOA-uVNTR) have been shown to exhibit a greater proclivity to engage in violent acts. Thus, we hypothesized that low-activity MAOA-uVNTR alleles may be associated with a higher risk for criminal violence among male offenders. To test this possibility, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(30 citation statements)
references
References 68 publications
0
28
1
1
Order By: Relevance
“…They also reported that the MAOA x parent criminality was associated with variation in individual arrest rates. Other studies of MAOA variants similarly linked lowactivity variants to criminal violence, and these effects have been reported among prisoners (Stetler et al, 2014). For instance, the rare 2-repeat allele of the MAOA gene has been linked to shooting and stabbing behaviors and to multiple shooting and stabbing behaviors among a sample of males from the Add Health (Beaver, Barnes, & Boutwell, 2013).…”
Section: Genesmentioning
confidence: 91%
“…They also reported that the MAOA x parent criminality was associated with variation in individual arrest rates. Other studies of MAOA variants similarly linked lowactivity variants to criminal violence, and these effects have been reported among prisoners (Stetler et al, 2014). For instance, the rare 2-repeat allele of the MAOA gene has been linked to shooting and stabbing behaviors and to multiple shooting and stabbing behaviors among a sample of males from the Add Health (Beaver, Barnes, & Boutwell, 2013).…”
Section: Genesmentioning
confidence: 91%
“…A number of studies have found a robust association between low-activity MAOA variants (and particularly 2-repeat alleles) and psychopathy and criminal behavior (Guo et al, 2008; Beaver et al, 2009; Beaver et al, 2010; Beaver et al, 2013; Beaver et al, 2014; Armstrong et al, 2014; Stetler et al, 2014; Tiihonen et al, 2015). The link with psychopathy, which has garnered this allele the questionable moniker of “psycho gene”, is particularly surprising, given the consolidated link of this trait with proactive aggression and callous-unemotional traits, rather than reactive aggression (Raine et al, 2006; Nouvion et al, 2007).…”
Section: Role Of Maoa Allelic Variants In the Ontogeny Of Aggressionmentioning
confidence: 99%
“…Many genes that have been implicated in depression, including brain-derived neurotrophic factor (BDNF), catechol-O-methyltransferase, and corticotropin-releasing hormone receptor 1, have more pronounced effects in the context of early-life stress (Heim and Binder, 2012). Enoch 2010, Kinnally 2009, Manuck 2000, Stetler 2014 No sex difference: Denotes studies in which gene-sex interactions were not found Sex difference: Denotes studies in which ( †) significant effects emerged for only one sex, ( ‡) significant effects emerged in opposite directions by sex, or interaction effects were different. Did not examine/Unclear: Denotes studies in which (1) only one sex was studied, (2) sex interactions were not ruled out, (3) marginally significant sex differences were found, or (4) sex differences were found in measures not included in the No sex difference: Denotes studies in which gene-sex interactions were not found Sex difference: Denotes studies in which ( †) significant effects emerged for only one sex, ( ‡) significant effects emerged in opposite directions by sex, or interaction effects were different.…”
Section: Potential Pathways Of Sex Modulation Of Genetic Polymorphismmentioning
confidence: 99%